2017
DOI: 10.1096/fj.201700296r
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertaseFurin1expression in theDrosophilafat body is essential for a normal antimicrobial peptide response and bacterial host defense

Abstract: Invading pathogens provoke robust innate immune responses in Dipteran insects, such as In a systemic bacterial infection, a humoral response is induced in the fat body. Gram-positive bacteria trigger the Toll signaling pathway, whereas gram-negative bacterial infections are signaled the immune deficiency (IMD) pathway. We show here that the RNA interference-mediated silencing of -a member of the proprotein convertase enzyme family-specifically in the fat body, results in a reduction in the expression of antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Furins are a family of evolutionarily conserved serine endoprotease enzymes that cleave precursor proteins into their mature forms ( 82 ). In accordance with our results, silencing of Drosophila Fur1 in the fat body has previously been shown to elevate the transcription of stress response genes including the JAK/STAT pathway target gene TotM ( 83 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furins are a family of evolutionarily conserved serine endoprotease enzymes that cleave precursor proteins into their mature forms ( 82 ). In accordance with our results, silencing of Drosophila Fur1 in the fat body has previously been shown to elevate the transcription of stress response genes including the JAK/STAT pathway target gene TotM ( 83 ).…”
Section: Discussionsupporting
confidence: 92%
“…While 4 to 5 SPs, and 1 to 2 CPs are typically been found in a range of both unicellular and multicellular organisms [1113], PCs show varied distribution across the tree of life, with yeast Saccharomyces cerevisiae species possessing 1 (Kexin) [4], D . melanogaster having 3 PCs, 2 of which being distinct variants of the same convertase ‘Furin’ [14], while Caenorhabditis elegans possesses 5, 2 of which (blisterase and aex-5) are nematode specific, with blisterase generating 9 isoforms [15]. Similarly, the SPs, PCs and CPs of other metazoa have been determined or predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The insect fat body acts as an immune barrier between the internal and external environment, which plays a major role in preventing infection by microbial, protozoan pathogens and other foreign objects [12, 13, 89]. In recent studies, a number of genes associated with immune response were identified from the fat body transcriptome of B .…”
Section: Resultsmentioning
confidence: 99%